Effects of CPAP on Testosterone Levels in Patients With Obstructive Sleep Apnea: A Meta-Analysis Study - Cignarelli, Angelo; Castellana, Marco; Castellana, Giorgio; Perrini, Sebastio; Brescia, Francesco; Natalicchio, Annalisa; Garruti, Gabriella; Laviola, Luigi; Resta, Onofrio; Giorgino, Francesco (Frontiers in Endocrinology, 2019)
Background: Obstructive sleep apnea (OSA) represents a frequent complication among patients with obesity and has been associated with neuroendocrine changes, including hypogonadism. Objective: We conducted a systematic review and meta-analysis to evaluate the effects of Continuous Positive Airway Pressure (CPAP) on testosterone and gonadotropins in male patients with OSA. Methods: The review was registered on PROSPERO (CRD42018103164). PubMed, Scopus, CENTRAL and Clinicaltrials.gov were searched until June 2018. Studies reporting the effect of CPAP on total testosterone, free testosterone, SHBG, FSH, LH and prolactin were included. A subgroup analysis on hypogonadal versus eugonadal status at baseline was performed. Results: Out of 129 retrieved papers, ten prospective cohort and two randomized controlled studies were included in the review. 388 patients were included. CPAP use was not associated with a significant change in total testosterone levels (mean difference 1.08, 95% CI -0.48 to 2.64) or other outcomes. The subgroup analysis confirmed the overall results. Conclusions: The present review does not support the hypothesis of a direct interaction between OSA and testosterone. Strategies other than CPAP should therefore be considered in managing hypogonadism in patients with OSA.